Food Preference of Buffalo in the Shepherd Area, Bukit District, Bener Meriah Regency - Reni Marlina; Abdullah Abdullah; Hasanuddin Hasanuddin; Khairil Khairil; Djufri Djufri (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Scientific studies on buffalo feed preferences (Bubalus bubalis Linn.) Are still lacking. Feed preference is the degree of preference for certain types of feed chosen by animals. This study aims to identify the types of feed plants consumed by buffalo, and to determine the level of buffalo feed preferences in the grazing area, Bukit District, Bener Meriah Regency. Collection of preference data is done by exploratory method and data collection is done by field survey. The research location is divided into three stations. Station I (grasslands), Station II (shrubs), and Station III (forest habitat). Feed preferences were analyzed using the Predation Index (IP) formula. Based on the results of the study found 23 species of feed plants that are included in 11 families. Species of plants that have a high level of preference are Eleusine indica (1.21), Axonopus compressus (1.19), and Sporobulus indicus (1.18) and forage plants that have low preferences, namely Musa paradisiaca (0.67), Sida rhombifolia (0.75), and Clinacanthus nutans (0.79).Keywords: Preferences, Types of Feed Plants, BuffaloKajian ilmiah tentang preferensi pakan kerbau (Bubalus bubalis Linn.) masih kurang dilakukan. Preferensii pakan adalah derajat kesukaan terhadap jenis pakan tertentui yangi dipilih hewan. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis tumbuhan pakan yang dikonsumsi oleh kerbau, dan mengetahui tingkat preferensi pakan kerbau di kawasan penggembalaan, Kecamatan Bukit, Kabupaten Bener Meriah. Pengumpulan data preferensi dilakukan dengan metode jelajah (eksploratif) dan pengambilan data dilakukan dengan cara survei lapangan. Lokasi penelitian terbagi menjadi tiga stasiun. Stasiun I (padang rumput), Stasiun II (semak belukar), dan Stasiun III (habitat hutan). Preferensi pakan dianalisis menggunakan rumus Indeks Pemangsaan (IP). Berdasarkan hasil penelitian ditemukan 23 jenis tumbuhan pakan yang termasuk kedalam 11 familia. Jenis tumbuhan pakan yang memiliki tingkat preferensi tinggi yaitu Eleusine indica (1,21), Axonopus compressus (1,19), dan Sporobulus indicus (1,18) dan tumbuhan pakan yang memiliki preferensi rendah yaitu Musa paradisiaca (0,67), Sida rhombifolia (0,75), dan Clinacanthus nutans (0,79).Kata Kunci: Preferensi, Jenis Tumbuhan Pakan, Kerbau